Improvisation in Music: Its Benefits, Uses, and Methods for Instruction - Harmon, Leah C. (My University, 2015)
For centuries, improvisation played an important role in Western music cultures. It was an expected music-making skill and used for self-expression and entertainment in everyday life. Improvisation dates back to the Middle-Ages when it was used during Gregorian chant in sacred church music. These chants began as syllabic settings of the text meaning that one syllable was sung per pitch. They gradually were embellished through improvisation to make the phrases melismatic, or singing one syllable over a series of several notes.1 Later, in the Baroque era, improvisation was required by keyboardists to “‘realize’ figured bass on the spot by improvising notes above a given bass line.”2 In the Classical era, virtuoso soloists would improvise the cadenzas of concertos during performances. Not only that, but a countless number of famous composers’ works throughout the Baroque, Classical and early Romantic time periods are assumed to have originated as improvisations. Improvisation began to take the back-burner in favor of literal performance of compositions towards the end of the nineteenth century.